Investment of temporarily free resources of Czech seniors - present and perspectives - Novotný Josef; Polách Jiří (Vysoká škola podnikání, 2014)
The article deals with investment of Czech seniors into investment instruments. This article aims to find out how seniors invest in investment instruments in the Czech Republic and how much of their retirement they are willing to invest. The main problem that occurs in the investment environment in the Czech Republic is a reluctance to invest public investment. The result is the finding whether the seniors investors invest or not, including the introduction of new knowledge arising from research conducted at the chosen target group on the basis of the questionnaire survey. Investors in retirement are an important group of investors in terms of population, where their number is growing every year. The disadvantage of the elderly is often neglected investment company with regard to their age and income.
Investování dočasně volných zdrojů českých seniorů - současnost a perspektivy
Keywords: senior; income; age; investment instrument; model; investment; senior; příjem; věk; investiční instrument; model; investování